Network pharmacology‐based exploration of gut microbiota‐derived metabolites for type‐2 diabetes - Widjaja, Nadia; Simatupang, Stefeny Theresia; Tan, Santi; Tjandrawinata, Raymond Rubianto (Universitas Gadjah Mada, 2025)
Probiotics confer health benefits and have been investigated for their potential therapeutic properties in type‐2 diabetes (T2D) treatment. This study employs a network pharmacology approach to explore gut microbiota‐derived metabolites that potentially alleviate T2D. Several strains and species of gut microbiota were identified that may produce metabolites with therapeutic potential for T2D. Interestingly, quercetin produced by Bacteroides uniformis and daidzein produced by Bifidobacterium adolescentis and Bifidobacterium breve have been studied for their antidiabetic effects. Using a network pharmacology approach, it was found that quercetin may target AKT1 and EGFR, critical proteins involved in insulin signaling pathways related to T2D. Additionally, 10‐oxo‐11‐octadecenoic acid produced by Lactobacillus plantarum and 10‐keto‐12Z‐octadecenoic acid produced by Lactobacillus paracasei were found to target PPARG, a gene regulating insulin signaling. These findings were further validated by the molecular docking analysis, which showed suitable to satisfactory binding strengths.